2006
DOI: 10.1097/01.brs.0000228724.01795.a2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Neurophysiologic Alerts During Anterior Cervical Spine Surgery

Abstract: Diagnosis of cervical spondylotic myelopathy or trauma and cervical corpectomy procedures increase the risk for having major intraoperative alerts. In case of persistent tceMEP/SSEP amplitude loss, consider delaying potentially harmful interventions, such as premature termination of the procedure or methylprednisolone infusion, until a new neurologic deficit is verified with an awake-clinical examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
87
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 11 publications
1
87
0
Order By: Relevance
“…According to other studies, 2,6,17 the definition of false-positive was based on neurological "events." However, our definition of false-positive was based on neurological de- terioration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to other studies, 2,6,17 the definition of false-positive was based on neurological "events." However, our definition of false-positive was based on neurological de- terioration.…”
Section: Discussionmentioning
confidence: 99%
“…The TcMEPs yielded a sensitivity of 75% and a specificity of 84%. Lee et al 6 reported a 60% amplitude criterion in 1445 anterior cervical surgeries. There were 267 TcMEP alerts (18.4%) and only 2 neurological deficits.…”
Section: Discussionmentioning
confidence: 99%
“…12 Two years later, the same group reported on their experience in a much larger cohort of patients. 15 This manuscript described the results of multimodality monitoring in 1445 patients undergoing ventral cervical surgery. Two hundred and sixty-seven patients were reported to have had either minor or major EP alerts, with the criteria for a major alert being identical to the criteria described above.…”
Section: 29mentioning
confidence: 99%
“…Two hundred and sixty-seven patients were reported to have had either minor or major EP alerts, with the criteria for a major alert being identical to the criteria described above. 15 Major EP alerts occurred in 16% of operations performed for CSM. Of the 93 major alerts in the CSM population, 44 occurred during surgery, 25 occurred during shoulder taping, and 13 occurred during neck taping.…”
Section: 29mentioning
confidence: 99%
“…LR between 1 and 2 and between 0.5-1 rarely alter pretest probability. 6 Despite traditional spinal IOM literature suggests that NIOM is effective in identifying patients at a high risk for sustaining new spinal cord injuries [7][8][9][10][11][12][13][14][15] as well as animal research has supported human experience, [16][17][18] there is a heterogeneity in IOM services and this should be reviewed to see what accounts for the difference in false-positive and false-negative cases in the literature.…”
Section: Resultsmentioning
confidence: 99%